Transcriptome and analysis on the complement and coagulation cascades pathway of large yellow croaker (Larimichthys crocea) to ciliate ectoparasite Cryptocaryon irritans infection. (March 2016) - Yin, Fei; Gao, Quanxin; Tang, Baojun; Sun, Peng; Han, Kunhuang; Huang, Weiqing
Abstract: Large yellow croaker ( Larimichthys crocea ) is one of the most valuable marine fish in southern China. Given to the rapid development of aquaculture industry, the L . crocea was subjected to ciliate ectoparasite Cryptocaryon irritans . It therefore is indispensable and urgent to understand the mechanism of L . crocea host defense against C . irritans infection. In the present study, the extensively analysis at the transcriptome level for Cryptocaryoniasis in L . crocea was carried out. These results showed that 15, 826, 911, 16, 462, 921, and 15, 625, 433 paired-end clean reads were obtained from three cDNA libraries (A: 0 theronts/fish, B: 12, 000 theronts/fish, and C: 24, 000 theronts/fish) of the L . crocea immune-related tissues by Illumina paired-end sequencing technology. Totally, 30, 509 unique transcript fragments (unigenes) were assembled, with an average length of 1715 bp. In B/A, C/A, and C/B pairwise comparison, 972, 900, and 1126 genes showed differential expression respectively. Differently expressed immune-related genes (DEIGs) were scrutinized, in B/A pairwise comparison, 48 genes showed differential expression, including 26 up-regulated genes and 22 down-regulated genes in B; in C/A pairwise comparison, there were 39 DEIGs, including 7 up-regulated genes and 32 down-regulated genes in C; in C/B pairwise comparison, 40 genes showed differential expression, including 11 up-regulated genes and 29 down-regulated genes in C. There were 16 DEIGs enriched KEGG pathways, in which the complement and coagulation cascades pathway was the top most DEIGs enriched pathway (B:A = 42; C:A = 28; C:B = 42). The coagulation and fibrinolytic system was in a highly active state after infected by C . irritans with non-lethal concentration; the alternative complement pathway may play an important role in the early stages of C . irritans infection. These results demonstrated that low-concentration infection can significantly induce the immunological response in fishes, however, when fishes were in fatal conditions, the immunity was suppressed. Highlights: Analysis at the transcriptome level for cryptocaryoniasis in Larimichthys crocea . 30, 509 unigenes were assembled, with an average length of 1715 bp. Coagulation and fibrinolytic system was activated after non-lethal concentration C . irritans infection. Alternative complement pathway plays an important role in the early stages of C . irritans infection. High concentration infection can significantly suppress the immunity.